Study of transient resistance of contact materials and contacts of electrical devices during interaction with aggressive environment - Korobskyi, V.; Chornovolenko, O. (Energy and Automation, 2023)
It is proposed to replace serial contact parts based on silver with experimental contact units based on copper. Climatic tests of contact materials were carried out to determine the performance and production operation of experimental contacts.As a result of the change in contact resistance and mass of samples of copper-based contact materials with thermodynamically stable impurities and on the basis of petrographic analysis of their interaction products, transient resistance and corrosion resistance of electrical contact materials in chemically active environments were evaluated. Stable transient resistance and high corrosion resistance of the studied materials in NH3 and CO2+H2O environments are shown.To determine the operability of the starters, tests were carried out on the reliability of contact of the starters. These studies were carried out for serial contact parts of PML-1100O4 electromagnetic starters based on silver - СрН-90, СрМ-0.2+М1 and metal-ceramic contact parts based on copper with metal impurities and defined thermodynamically stable compounds. Contact units of the starters, made of experimental contact materials, have passed several years of production tests in real agricultural conditions.The reliability of the electrical contact is largely determined by the components that make up its composition, the structure and properties of the surface layers, which are formed as a result of erosion and transfer of the contact material in the electric arc.The main component for the contact materials of the most common electromagnetic starters is silver.Corrosion of the working surfaces of the contacts of the starters, which occurs under the influence of chemically active impurities in the environment, is also one of the main factors of wear and failure. Contacts of PML, PM, PMM, PME, PMA, PAE starters are made of silver-based material (СрН-90, СрМ-0.2+М1, СОК-15, КМК-А10м, etc.).Since the reliability of starters with developed test contacts involves the preservation over time of the parameters that characterize the ability of electromagnetic starters to perform their functions in all prescribed modes and in harsh operating conditions (environmental conditions of technological animal husbandry premises), the reliability indicators are controlled during all tests: when monitoring the functioning of the starter and when testing for the influence of external factors (control tests). In order to reduce the time and means of testing, one-stage control is used, in which one sample is tested (based on the results of the test, a decision is made about compliance with reliability requirements).As a rule, the technological equipment of livestock farms and complexes mainly includes electromagnetic starters of general industrial purpose of wear resistance class B, B. Such starters are unsuitable for long-term operation in specific conditions of agriculture, as they do not meet the requirements for protection against environmental influences, fail before reaching a certain resource of wear resistance, and this primarily concerns the contact system (up to 30% of all starter failures). Today's modern electrical engineering industry does not produce starters and relays for the needs of the agro-industrial sector.In order to improve the reliability of the contact system of the electromagnetic starter and relay in general, it is suggested to replace the serial contact parts with copper-based contact parts.The aim of the study -carrying outcomparative studies of the characteristics of electromagnetic starters with serial and experimental test contact parts and the identification of the influence of aggressive environment parameters on the nature of changes in the transient resistance of contact materials and contacts of starters.Key words: transient resistance, contact part, contact material, climatic tests, switching tests, corrosion resistance, electrical apparatus, reliability